On Materials Use Training in EFL Teacher Education : Some Reflections (2006)
ABSTRACT: This paper reports on the findings of a case study carried out at Universidad de Antioquia as well as explores training on materials use in our teacher preparation program and its effectiveness in the practicum. The data analyzed suggest that, although teacher educators having new approaches to train future teachers in materials use, they still need to revise the way they include this component in teacher preparation curricula. Training in the use of materials should include their use in settings with limited resources as well as those with greater possibilities in technical and non-technical materials. Lastly, the author raises awareness about the need to include materials use as an issue in local and national EFL teacher education agendas.